Analysis of the Effect of Business Diversification and Derivative Disclosures on Tax Avoidance in Manufacturing Companies Listed on IDX - Utama, Denny; Lindrianasari, Lindrianasari; Syaipudin, Usep (Universitas Pendidikan Indonesia, 2020)
One of the obstacles to accelerating national development is the existence of tax evasion activities or what is commonly referred to as tax avoidance. It is estimated that there are 110 trillion rupees each year, the figure for tax evasion. Most are business entities, around 80%, the rest are individual taxpayers. This study aims to examine the effect of diversification of activities and disclosure of derivative transactions on tax evasion activities. The research was conducted on manufacturing companies listed on the Indonesia Stock Exchange from 2014 to 2018, with a sample of 92 companies. The data analysis method for this study used multiple linear regression. The results prove that corporate diversification as measured by the hirschman-herfindhl index has no effect on tax avoidance activity. Meanwhile, the derivative transaction disclosure variable as measured by the disclosure score has an effect on tax avoidance activities.